Expression Study of Proline-rich EVHl Ligand (Prel)Family Gene in Zebrafish (Danio rerio) - Pang, Shek Li (Universiti malaysia sarawak (UNIMAS), 2017)
proline-rich EVH I ligand (Prel) family belongs to Mig-IO/RIAMILamellipodin of adaptor proteins (MRL). They share Pleckstrin homology (PH) and Ras-associating (RA) domain which contains the potential profilin-and EnaIV ASP binding sites. Prell is involved in integrin activation while Prel2 have significant function in cell signaling, cell migration, promoting axon guidance, affecting. adhesion and regUlating lamellipodial dynamics. However, only Northern analysis is available of selected adult organs in human and mice and the expression profiles have not been characterized in other animal model. In this project, Prel gene family (Prell, Prel2a and Prel2b) in zebrafish have been identified and characterized. Prel2 was found to have two copies due to duplication-degeneration-complementation (DDC) effect. RT-PCR analysis showed that Prel family genes commenced after IK cells stage (3 hour post fertilization (hpf), where the zygotic transcription starts until 5 day post fertilization (dpf). The expression profiles of Prel genes at 24hpf and 34hpf were established. Expression of Prel2a and Prel2b genes due to the DDC effect, Prel2a and Prel2b complement each other to function as whole Prel2 during the embryogenesis while Prell remained widely and diffusely expressed at 24hpf and 34hpf. Prel family members are suggested to be involved in somite development of zebrafish.